Ethics in the global South - Schwartz, Michael active 2017; Harris, Howard active 2017 (Research in ethical issues in organizations)
Prelims -- Ethics in the global South -- War and famine around the Indian Ocean during the Second World War -- Bringing international sustainability guidelines home: a case study of a mega South African state-owned enterprise -- Religion as apparatus of ethical similarity: a catalyst towards the Framework of Ethical Behaviors (FEB) in technical environment -- Modern business and the doctrine of the mean -- Gift giving, guanxi, bribery and corruption challenges in Australia-China Business: An ethical tension between the Global South and the East -- A short history of applied ethics in Australia -- Ethics and the unified justice examination of the People's Republic of China -- Reviews